Tensile Behavior of High Performance Structural Steel T-stub Joints - Zhao, Ming Shan (2016)
In this study, experiments were conducted to investigate the tensile behavior of ten T-stub joints made of different types of high performance structural steel including the Reheated, Quenched and Tempered (RQT) grade S690 high strength steel, the Thermal-Mechanical Controlled Processed (TMCP) grade S385 and S440 structural steels. The results were further validated against the analytical yield line method and the design resistance equations provided by the EC3. It is found that the behavior of the T-stub joints made of S385 and S440 steels reasonably agreed with analytical approach and the predictions by the EC3. However, although the S690 specimens showed higher design resistance than the S385 and S440 specimens with the same thickness, the results were significantly lower than both the predictions by the analytical approach and the EC3. In addition, the ductility of the S690 specimens is also found to be significantly lower than that of the S440 and S385 specimens and failed in more brittle failure modes.